'Constituent Covid-19 apocalypses: contagious conspiracism, 5G, and viral vaccinations'. Issue 1 (4th May 2021) - Sturm, Tristan; Albrecht, Tom
Abstract: The uncertainties and scale of the Covid-19 pandemic has mobilised global anxieties and insecurities, and many cultural groups have conjuncturally embedded conspiracy theories within millennial and apocalyptic thought to explain and find meaning in the pandemic. The apocalypse lends itself well to conspiratorial thinking because conceptually it is flexible enough to reflect any crisis. To this end, the global development of Covid-19 conspiracism is what the authors term 'contagious conspiracism' which is defined as viral global cultural conspiracism. The paper explores how millennialist responses to Covid-19 in various media outlets transcend academic categories of analysis and cultural boundaries between, say, religious and secular, far-right and radical left. First explored is how the crisis became embedded in established (mainly American) contemporary millennial beliefs and prophecies through selected far-right, evangelical and radical left narratives. Second, it is shown how these theories have been 'improvised' to include 5 G and also travelled to Europe and taken on geographical significance in Belfast and Berlin. Third, the authors illustrate the shared ingredients, motivations, and semiotics across apocalyptic conspiratorial Covid-19 narratives, all of which resonate with concerns about power, specifically emergent surveillance technologies, governmental abuse of power, and neoliberal capital, with divergent truths about who is blame from 5 G/vaccine theories to corporate technocapitalism. The paper concludes that these shared discourses across apocalyptic and conspiratorial Covid-19 narratives mean many of us are conspiracists and/or conspiracy theorists at some level and is therefore both revealing of the similarities and has the potential to create democratic constituencies.